Eight weeks of aromatase inhibition using the nutritional supplement Novedex XT: Effects in young, eugonadal men - Willoughby, D. S.; Wilborn, C.; Taylor, L.; Campbell, W. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
This study examined the effects of an aromatase-inhibiting nutritional supplement on serum steroid hormones, body composition, and clinical safety markers. Sixteen eugonadal young men ingested either Novedex XT™ or a placebo daily for 8 wk, followed by a 3-wk washout period. Body composition was assessed and blood and urine samples obtained at weeks 0, 4, 8, and 11. Data were analyzed by 2-way repeated-measures ANOVA. Novedex XT resulted in average increases of 283%, 625%, 566%, and 438% for total testosterone (P = 0.001), free testosterone (P = 0.001), dihydrotestosterone (P = 0.001), and the testosterone:estrogen ratio (P = 0.001), respectively, whereas fat mass decreased 3.5% (P = 0.026) during supplementation. No significant differences were observed in blood and urinary clinical safety markers or for any of the other serum hormones (P > 0.05). This study indicates that Novedex XT significantly increases serum androgen levels and decreases fat mass.